Selection of The Cirebon-Semarang High Speed Railway Phase I (Cirebon-Brebes) Using Arcgis 10.8 - Suriadilaga, Muhammad; Aghastya, Adya; Danartini, Riska Sasanti (Nusantara Publisher, 2024)
The high-speed railway line has great potential to increase economic growth in the area through which it passes, especially the area that is a transit point or stop of the train. In accordance with the National Railway Master Plan (RIPNAS) the development of high-speed railways in Indonesia will continue to the city of Surabaya. The purpose of this research is to plan the Cirebon-Semarang Phase I (Cirebon-Semarang) high-speed railway with reference to the starting point of research from previous studies. The data needed are land use, disaster, and topography data as secondary data that are processed using ArcGIS 10.8. This research is including the selection of the best traces using simple multi-criteria analysis. The alternative that was selected as the best alternative route from the results of a simple multi-criteria analysis is alternative 2 with a route length of 43.2 km.